Growth enhancement and extenuation of drought stress in maize inoculated with multifaceted ACC deaminase producing rhizobacteria - Ojuederie, Omena Bernard; Babalola, Olubukola Oluranti (Frontiers in Sustainable Food Systems, 2023)
Introduction Maize is a major staple cereal crop grown and consumed globally. However, due to climate change, extreme heat and drought stresses are greatly affecting its production especially in sub-Saharan Africa. The use of a bio-based approach to mitigate drought stress is therefore suggested using plant growth-promoting rhizobacteria (PGPR). Methods This study investigated the abilities of 1-aminocyclopropane-1-carboxylate (ACC) deaminase producing PGPR Pseudomonas sp. MRBP4, Pseudomonas sp. MRBP13 and Bacillus sp. MRBP10 isolated from maize rhizosphere soil, to ameliorate the effect of drought stress in maize genotypes MR44 and S0/8/W/I137TNW//CML550 under two water regimes; mild drought stress (50% FC) and well-watered conditions (100% FC). The rhizobacterial strains were identified by 16S rRNA sequencing and biochemical tests, and evaluated for plant growth-promoting and abiotic stress tolerance traits. Results and discussion The synergistic effect of the bacterial strains had a highly significant (p < 0.001) effect on the total soluble sugar, soil moisture content and relative water content, which were enhanced under water-stress in the inoculated plants. Relative water content was significantly highest (p < 0.001) in maize plants co-inoculated with Pseudomonas sp. MRBP4 + Bacillus sp. MRBP10 (60.55%). Total chlorophyll content was significantly enhanced in maize seedlings sole inoculated with Pseudomonas sp. MRBP4, Pseudomonas sp. MRBP13, and co-inoculated with Pseudomonas sp. MRBP13 + Bacillus sp. MRBP10 by 15.91%, 14.99% and 15.75% respectively, over the un-inoculated control. Soil moisture content increased by 28.67% and 30.71% compared to the un-inoculated control when plants were inoculated with Pseudomonas sp. MRBP4 + Bacillus sp. MRBP10 and Pseudomonas sp. MRBP4 + Bacillus sp. MRBP10 respectively. The interactive effect of genotype × bacteria significantly enhanced biomass production. Leaf area was highest in maize plants co-inoculated with Pseudomonas sp. MRBP4 + Pseudomonas sp. MRBP13 (212.45 ± 0.87 cm2) under drought stress. Treatment of maize seeds with Pseudomonas sp. MRBP 4 + Pseudomonas sp. MRBP13 + Bacillus sp. MRBP10 significantly increased the root length (10.32 ± 0.48 cm) which enhanced survival of the maize seedlings. Bioinoculation of maize seeds with these strains could boost maize production cultivated in arid regions.